Individual differences in self-presentational motives in daily social interactions - Nezlek, John B.; Leary, Mark R. (Sage Publications, 2002)
In a study of self-presentational motives in everyday social encounters, 164 first-year and upper-class undergraduate students described their social interactions for 1 week using a variant of the Rochester Interaction Record. These descriptions focused on the strength of self-presentational motives and concerns for others? evaluations. Participants also completed measures of individual differences hypothesized to be relevant to self-presentation, which formed four distinct factors. A series of multilevel random coefficient modeling analyses found that individual differences in factors labeled Impression Motivation, Impression Construction Positivity, and Impression Construction Appropriateness were positively related to participants? nervousness in interaction and individual differences in Impression Motivation were positively related to the strength of self-presentational motives in interaction. A fourth factor, Negative Self-Evaluation, was positively related to the strength of participants? self-presentational motives for first-year students but negatively related to self-presentational motives for upper-class students, and Negative Self-Evaluation was related to self-presentation differently for men and women.